Tecendo a (re)significação - identidade nacional em Triste Fim de Policarpo Quaresma - Bristott, Maria Isabel (2009)
This dissertation takes as its basis the interpretation of Afonso Henriques Lima Barreto point of view (1881 1922) when he created the narrative, as well as the character, named Policarpo Quaresma his actions and his thoughts , in the novel Triste fim de Policarpo Quaresma (1911), in order to analyze and reflect upon the articulation between the national identity and the constitution of the identity/ subjectivity of the person and of the common reader. The study objectives are: to verify how the narrator tells the story, using the repetitive elements characterized by successive disappointments and repression events experienced by the protagonist; relate actions and thoughts of the main character by means of observation of the disappointments and the ideal of a person invested against the positivist movement during the First Republic (1891-1894), in the government of Floriano Peixoto; reflect on the author s intention regarding some names, both of the people as of the places presented in the story, and the contribution of that aspect in the articulation between the national identity and the constitution of the identity/subjectivity of the person; extend the literary criticism of the author, investing in the look of Policarpo on the actions propelled by an ideal and on how the protagonist stand in the face of the dominant forces in the Brazilian social, political, economic and cultural context. For the analysis of the text, the literary theory as well as the psychoanalysis fundamentals are employed in order to establish an inter, intra and transdisciplinary dialogue, contributing to the actions that constitute the national identity, so that they are more connected with human subjectivity and supported by education and culture